PERBANDINGAN ANTARA ASPEK HUKUM PERBANKAN DALAM SYARIAH DAN HUKUM PERBANKAN KONVENSIONAL - sugih ayu pratitis (Jurnal Perspektif Hukum, 2020)
It cannot be denied that development requires significant and sustainable funding. In the case of mobilizing public funds, the role of banking institutions cannot be ruled out. Bank as an institution that works based on public trust, has a very strategic role and position in national development. As an intermediary institution for public finance, the bank becomes the intermediary media for those who have excess funds and those who lack. Based on data findings, in Indonesia banking institutions have a mission and function as development agents, namely as an institution that aims to support the implementation of national development in order to improve equity, economic growth and national stability towards improving the welfare of the people at large. Banks in addition to influencing the business world have also absorbed a lot of labor. The development of the world economy is moving rapidly along with the progress of the economy that continues to develop in a country.